Vers l’émergence d’un modèle du quartier commercial transnational ? Les quartiers du made in China au Caire et à Oran - Anne Bouhali (M@ppemonde)
This paper compares the urban development of two marketplaces specialised in retail and wholesale trade of made-in-China goods since the 1990s: Medina J’dida in Oran (Algeria) and the Muski in Cairo (Egypt). In response to the expansion of trade routes between Asia and the Arab world, a new, import district model is under development in the region. The globalisation of commodity flows and human mobilities thus results in a standardisation of urban forms in transnational trade districts.